Prevalence of total hip and knee arthroplasty in former National Football League players: comparison with the general US population and other populations of professional athletes. Issue 1 (4th September 2020) - Tenforde, Adam S; Cortez, Bryan; Baker, Jillian; Borg-Stein, Joanne; Wasfy, Meagan; Baggish, Aaron L; Zafonte, Ross
Abstract : Objectives: To evaluate the prevalence of total hip arthroplasty (THA) and total knee arthroplasty (TKA) in a population of former National Football League (NFL) players. Methods: Participants were 3913 former NFL players (participation in years 1960–2019) who completed either an online or mailed survey that included self-reported TKA and THA, year(s) of surgery and date of birth. The prevalence of TKA and THA was reported by age category and compared to published cohorts of athlete populations and general population of non-athletes in the USA. Results: 12.3% and 8.1% of sample reported TKA and THA, respectively. The prevalence of both TKA and THA was higher in former NFL players compared to US non-athletes across all ages. Prevalence of TKA was not statistically higher than in other former athlete cohorts but performed at younger ages. The prevalence of TKA and THA was higher than in other cohorts of former NFL players. Conclusion: Former NFL players had higher prevalence of arthroplasty than the general population, suggesting prior participation in American-style football may contribute to elevated risk for arthroplasty at younger ages. Understanding risk factors in style of play, lifestyle and other contributors is important to improve joint health of this population.